The protective PLCγ2-P522R variant mitigates Alzheimer’s disease-associated pathologies by enhancing beneficial microglial functions - Takalo, Mari; Jeskanen, Heli; Rolova, Taisia; Kervinen, Inka; Hellén, Marianna; Heikkinen, Sami; Koivisto, Hennariikka; Jokivarsi, Kimmo; Müller, Stephan A.; Koivumäki, Esa-Mikko; Mäkinen, Petra; Juopperi, Sini-Pauliina; et al. (Springer Science and Business Media LLC, 2025)
Background: Phospholipase C gamma 2, proline 522 to arginine (PLCγ2-P522R) is a protective variant that reduces the risk of Alzheimer's disease (AD). Recently, it was shown to mitigate β-amyloid pathology in a 5XFAD mouse model of AD. Here, we investigated the protective functions of the PLCγ2-P522R variant in a less aggressive APP/PS1 mouse model of AD and assessed the underlying cellular mechanisms using mouse and human microglial models.
Methods: The effects of the protective PLCγ2-P522R variant on microglial activation, AD-associated β-amyloid and neuronal pathologies, and behavioral changes were investigated in PLCγ2-P522R knock-in variant mice crossbred with APP/PS1 mice. Transcriptomic, proteomic, and functional studies were carried out using microglia isolated from mice carrying the PLCγ2-P522R variant. Finally, microglia-like cell models generated from human blood and skin biopsy samples of PLCγ2-P522R variant carriers were employed.
Results: The PLCγ2-P522R variant decreased β-amyloid plaque count and coverage in female APP/PS1 mice. Moreover, the PLCγ2-P522R variant promoted anxiety in these mice. The area of the microglia around β-amyloid plaques was also increased in mice carrying the PLCγ2-P522R variant, while β-amyloid plaque-associated neuronal dystrophy and the levels of certain cytokines, including IL-6 and IL-1β, were reduced. These alterations were revealed through [18F]FEPPA PET imaging and behavioral studies, as well as various cytokine immunoassays, transcriptomic and proteomic analyses, and immunohistochemical analyses using mouse brain tissues. In cultured mouse primary microglia, the PLCγ2-P522R variant reduced the size of lipid droplets. Furthermore, transcriptomic and proteomic analyses revealed that the PLCγ2-P522R variant regulated key targets and pathways involved in lipid metabolism, mitochondrial fatty acid oxidation, and inflammatory/interferon signaling in acutely isolated adult mouse microglia and human monocyte-derived microglia-like cells. Finally, the PLCγ2-P522R variant also increased mitochondrial respiration in human iPSC-derived microglia.
Conclusions: These findings suggest that the PLCγ2-P522R variant exerts protective effects against β-amyloid and neuronal pathologies by increasing microglial responsiveness to β-amyloid plaques in APP/PS1 mice. The changes observed in lipid/fatty acid and mitochondrial metabolism revealed by the omics and metabolic assessments of mouse and human microglial models suggest that the protective effects of the PLCγ2-P522R variant are potentially associated with increased metabolic capacity of microglia.